Biosynthesis of irregular monoterpene lavandulol in Saccharomyces cerevisiae - Shengxin Nie; Ruiqi Chen; Mingyue Ge; Yue Qu; Xiaofeng Liu; Chaofeng Ruan; Xiaoguang Yan; Jianjun Qiao (Synthetic and Systems Biotechnology)
Lavandulol, the primary chemical constituent of lavender essential oil, is an irregular monoterpene present in Lavandula angustifolia. It has been employed in the spice and cosmetic industries owing to its pleasing aromatic properties. In addition, its efficacy as an inhibitor of insect mating behaviour has led to incorporation within synthetic pheromone formulations. With the development of synthetic biology, more terpenoids are synthesized utilizing microorganisms. In this study, lavandulol was biosynthesized in Saccharomyces cerevisiae for the first time. An initial screening of lavandulyl diphosphate candidates was performed to identify enzymes compatible with heterologous expression in yeast. To increase the supply of DMAPP, the key enzymes of the MVA pathway, IDI1 and tHMG, as well as IDI1, ERG12, and ERG8 were overexpressed. Furthermore, the metabolic flow loss of acetyl-CoA and DMAPP was also reduced by deleting the genes of MLS1 and CIT2, as well as replacing the ERG20 promoter. Through the modification of lavandulyl diphosphate synthase, the flask titer was increased to 136.68 mg/L. Finally, the highest reported level of lavandulol production (308.92 mg/L) in S. cerevisiae was achieved by fed-batch fermentation in a 5 L bioreactor. To our knowledge, this is the first report of heterologous biosynthesis of lavandulol in S. cerevisiae.